The The Political Relevance of Kartosuwiryo's Hijrah in the Global Context: Inspiration for Struggle in the Modern Era - Endang Susanti (Journal of Islamic History and Manuscript, 2025)
Sekarmadji Maridjan Kartosuwiryo, familiarly called Kartosuwiryo, was the proclamator of the Islamic State of Indonesia. Kartosuwiryo believed Islam had a significant influence on every aspect of human life. The idea he wanted to realize was establishing the Islamic State of Indonesia, and hijrah politics was one of Kartosuwiryo's efforts toward the Islamic State of Indonesia. This article will analyze the basic concept of the hijrah political thought of Sekarmadji Maridjan Kartosuwiryo in establishing the Islamic State of Indonesia. The method used is qualitative, with literature studies such as books, journals, articles, and others. In addition, the author uses a historical approach and the construction of a day approach to explore information about Kartosuwiryo's hijrah politics. The results showed that Kartosuwiryo's hijrah politics was an Islamic-based struggle to build a state with laws and order based on the Qur'an. This concept remains relevant to address modern global challenges, such as migration, religious identity, and cross-cultural solidarity. In addition, this article also shows that the politics of hijrah is not only a strategy of resistance against colonialism but also has relevance in the modern era. Hijrah can be translated as an effort to create social transformation, such as community empowerment, cross-cultural solidarity, and humane management of global migration. By adapting to digital technology, the concept of hijrah can also encourage interfaith dialogue and spread social justice values in an increasingly connected world.